OP0114 Secukinumab for The Treatment of Ankylosing Spondylitis: Comparative Effectiveness Results versus Adalimumab Using A Matching-Adjusted Indirect Comparison. (15th July 2016) - Maksymowych, W.; Strand, V.; Baeten, D.; Nash, P.; Thom, H.; Cure, S.; Palaka, E.; Gandhi, K.; Richards, H.; Jugl, S.
Abstract : Background: Secukinumab 150 mg (SEC) is approved for the treatment of active AS in adults with inadequate response to conventional therapy. The MEASURE 2 (M2) trial showed superiority for SEC over placebo for the primary outcome measure, ASAS20 response, at week 16 and for multiple secondary outcomes. Efficacy was sustained up to 2 years. The ATLAS trial compared adalimumab 40 mg (ADA) with placebo, but there is no head-to-head trial of SEC vs. ADA. Placebo patients could switch to active treatment as early as week 12 in ATLAS and at week 16 in M2. Matching-adjusted indirect comparison (MAIC) can assess comparative effectiveness by re-weighting patient level data (PLD) resulting in a reduced effective sample size (ESS), to match the baseline patient characteristics of another trial. Thus, MAIC is able to simulate head-to-head comparisons. Objectives: To assess the relative efficacy of SEC vs. ADA using adjusted PLD from M2 and published ATLAS data. Methods: PLD from the SEC arm in M2 (n=72) was re-weighted to match baseline characteristics of the ADA arm in ATLAS (n=208). Logistic regression was used to determine weights for age, sex, mean BASFI score, mean CRP level, and prior biologic use. Sensitivity analyses including adjustment for BASDAI score were performed. Correlation analyses of baseline characteristics with ASAS20/40 responses were not available before the regression analyses. Both trials reported non-responder imputation (NRI) results until week 24; beyond which ATLAS used LOCF with n=311, including placebo switchers. Weighted outcomes from M2 (ESS n=34) were compared with outcomes from ATLAS. Pairwise comparisons using relative risks (RR) were performed. Results are presented as probability of response (95% CI) and RR (95% CI). Results: SEC treatment led to statistical significantly higher ASAS responses at week 24 vs. ADA for ASAS20 (72.3% [62–83]; RR 1.43 [1.12–1.84] p =0.004) and ASAS40 (61.4% [50–73]; RR 1.56 [1.14–2.14] p =0.006). The ASAS20 and 40 response rates for ADA were 50.5% (44–57) and 39.4% (33–46) respectively. At week 52, SEC led to higher ASAS responses vs. ADA. The ASAS20 and 40 response rates for SEC were 78.9% (69–89) and 57.6% (46–69) respectively, and for ADA were 65.4% (60–71) and 47.1% (42–53). The SEC vs. ADA comparison at ASAS20 approached significance (RR 1.21 [0.996–1.461] p =0.055). No significant differences were observed at week 12 and 16. Sensitivity analyses support these findings. Conclusions: SEC demonstrated statistically significant higher symptomatic improvement in terms of ASAS20 and 40 responses vs. ADA at week 24 in this first MAIC in AS. A similar trend was noted up to week 52, even though SEC NRI data was compared with ADA LOCF data at week 52. Differences in study designs, such as the early-escape criteria and disease duration together with the small ESS (n=34) for SEC may result in potential limitations, warranting further MAIC analyses in AS. Disclosure of Interest: W. Maksymowych Grant/research support from: Abbvie, Pfizer, Sanofi, Consultant for: Abbvie, Amgen, Boehringer, Eli-Lilly, Janssen, Merck, Pfizer, Sanofi, UCB, V. Strand Consultant for: Abbvie, Amgen Corporation, AstraZeneca, BMS, Celgene, Celltrion, CORRONA, Genentech/Roche, GlaxoSmithKline, Janssen, Jazz Pharmaceuticals, Lilly, Novartis, Pfizer, Regeneron, Sandoz, Sanofi and UCB, D. Baeten Grant/research support from: Pfizer, MSD, AbbVie, UCB, Novartis, Janssen and Boehringer Ingelheim, Consultant for: Pfizer, MSD, AbbVie, UCB, Novartis, Janssen, Boehringer Ingelheim, Eli Lilly, Roche, BMS and Glenmark, P. Nash Grant/research support from: Novartis, Consultant for: Novartis, H. Thom Consultant for: Novartis Pharma AG and for a short time in 2015 for Eli Lilly, S. Cure: None declared, E. Palaka Employee of: Novartis, K. Gandhi Shareholder of: Novartis, Employee of: Novartis, H. Richards Shareholder of: Novartis, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis